STRUKTUR DAN PENYEBARAN VEGETASI STRATA SAPLING DI KAWASAN HUTAN MANGROVE PULAU BENGKALIS PROVINSI RIAU - Yuslim Fauziah; Nursal '; Supriyanti ' (Biogenesis, 2004)
The  research  about  structure  and  distribution  of sapling  strata  vegetation  has  been  done  at  mangrove forest ecosystems  in Bengkalis  Islands  Riau Province  from  March until November 2002. This study used quadrate methods  with quadrate was placed  along o f transect.  Ten quadrate  (10x5 m ) was make on the transects   with   systematically   systems,   Observation   variable   are   Relative   Density   (KR),   Relative frequency  (FR),  Relative  Dominance  (DR)  and  Informace  Value.  The results  of data   analysis  showed that  generally  was  founded  21  species  frok,  sapling  stratum,  That  dominance  species is Rhyzophora apiculata (132,79% ) at  location  VII (Desa  Selat  Baru),  that what  founded  2 sapling  strata  vegetation (Rhizophora  apiculata dan  Rhizophora  mucronata)  has  been  distributed   all  o f area  study  (100%),  at mangrove  forest of Bengkalis  Islands   Key words : Mangrove, structure,  strata,, sapling, vegetation